Self-Assembly of Janus Type Amphiphilic Dendrimers from Dissipative Particle Dynamics Simulation. (November 2020) - Yan, Wenyuan
Abstract: The self-assembly of Janus type amphiphilic dendrimers has been studied extensively through experiments and computer simulations, while most of the simulations assume that Janus molecules are connected by covalent bonds, disregarding the noncovalent interaction which evokes the particular dynamic self-assembly regulation. This paper investigates the dynamic self-assembly behavior of Janus type amphiphilic dendrimers through the dissipative particle dynamics (DPD) method. A series of coarse-grained models of Janus type amphiphilic dendrimers with different hydrophobic-hydrophilic ratios were constructed to simulate the static self-assembly, and then the dynamic self-assembly was carried out through introducing a chemical bonding reaction to simulate the non-covalent interaction between the two different parts of Janus type dendrimers. The control of reaction rate was accomplished by modifying the reaction probability to adjust the dynamic self-assembly process. The results indicate that the introduction of non-covalent interaction changes the self-assembly behavior of some models and generates different dynamic self-assembly structures. It can also be deduced that the reaction rate exerts influence on the structure of dynamic self-assembly.